Comparative Studies In Rumen Activities And Urea Kinetics Between Cattle And Buffaloes - Abdullah, NorHani (1989)

(untitled)
Studies in rumen activities and urea kinetics were conducted to compare the digestion between cattle and buffaloes fed fibrous diets. On straw-based diets , buffaloes demonstrated higher rate of rumen fermentation . The rumen pH of buffaloes ( 6.46+0.02) was lower than cattle (6.78+0.02) , while the VFA concentration was higher than that of cattle (98.0+2.2 versus 85.5+1.6 romo1/1 ) . The rumen ammonia was also found to be higher in buffaloes (4.00+0.08mg N/100ml) than in cattle (3.55+0.08mg N/ 100 ml ) . The rate of degradation of straw-1 was also faster in buffaloes (0.018 ± 0.003 h ) than in cattle-1 (0 . 010 + 0.004 h ) . A similar trend was observed when the animals were fed guinea grass. Voluntary feed intake and water consumption were similar for both species fed grass, but when fed fed straw, cattle showed higher feed intake and lower water consumption than buffaloes. There was no difference between cattle and buffaloes in the rate of passage of small feed particles from the rumen and rumen fluid volume based on liveweight was also not significantly different between the two animal species. However, the fluid outflow rate from the rumen was slower in the buffaloes (1.06 +0.9 1/h) than in the cattle (1.55 ± 0. 01 1/h).